The human as paradox and taboo - Gans, Eric Lawrence (2024)
The notion of paradox may be said to begin with Zeno and Achilles never catching the tortoise, which we found in Chronicles 515-516 to be equivalent to Mahayana Buddhist Nagarjuna’s idea of the traveler who never travels: something obviously possible in reality becomes "unthinkable" when the language used to describe it is subjected to an...